Gods of Newport - Jakes, John (New York : Signet, 2007)
Determined to secure entry into the elite social circles of late nineteenth-century Rhode Island, Sam Driver enlists the help of a pair of social gadflies but finds his efforts complicated by his daughter's romance with an impoverished young Irishman.
Keywords: Upper class; Newport (R.I.); United States -- Social life and customs -- 19th century; Historical fiction